Promoter Hypermethylation of the EMP3 Gene in a Series of 229 Human Gliomas - Mellai, Marta (Hindawi Publishing Corporation, 2013)
The epithelial membrane protein 3 (EMP3) is a candidate tumor suppressor gene in the critical region 19q13.3 for several solid tumors, including tumors of the nervous systems. The aim of this study was to investigate the EMP3 promoter hypermethylation status in a series of 229 astrocytic and oligodendroglial tumors and in 16 GBM cell lines. The analysis was performed by methylation-specific PCR and capillary electrophoresis. Furthermore, the EMP3 expression at protein level was evaluated by immunohistochemistry and Western blotting analysis. Associations of EMP3 hypermethylation with total 1p/19q codeletion, MGMT promoter hypermethylation, IDH1/IDH2 and TP53 mutations, and EGFR amplification were studied, as well as its prognostic significance. The EMP3 promoter hypermethylation has been found in 39.5% of gliomas. It prevailed in low-grade tumors, especially in gliomas with an oligodendroglial component, and in sGBMs upon pGBMs. In oligodendroglial tumors, it was strongly associated with both IDH1/IDH2 mutations and total 1p/19q codeletion and inversely with EGFR gene amplification. No association was found with MGMT hypermethylation and TP53 mutations. In the whole series, the EMP3 hypermethylation status correlated with 19q13.3 loss and lack of EMP3 expression at protein level. A favorable prognostic significance on overall survival of the EMP3 promoter hypermethylation was found in patients with oligodendroglial tumors.